The Effectiveness of Pineapple Extract (Ananas Comosus) and Kesum Leaves (Polygonus Minus) on the Quality of Coconut Oil (Coconus Nucifera) - Hendra Budi Sungkawa; Wahdaniah Wahdaniah; Herlinda Djohan (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
The processed oil from the coconut plant is generally understood as coconut oil. A method is required to produce a product with a higher oil extraction rate and is able to reduce the water content and free fatty acids in the coconut oil production. It is also necessary to add substances that can delay or prevent fat oxidation reactions by generating substances in the form of antioxidants. The method that can be implemented is the enzymatic method employing the bromelain enzyme in a pineapple with the addition of an antioxidants substance from the kesum leaf. The objective of this research is to describe the quality of coconut oil after the addition of pineapple (ananas comosus) and kesum leaves (polygonus minus) extracts. The parameters for describing the quality of the oil are the organoleptic test, the degree of acidity, the oil extract rate, the peroxide number, the saponification number, and the acid number. This research is a quasi-experiment. The samples in this research were coconut oil without the addition of pineapple fruit extract, coconut oil with the addition of pineapple fruit extract without the addition of kesum leaves, and coconut oil with the addition of pineapple fruit extract and kesum leaves as much as 20gr, 30gr and 40gr. Based on the statistical results of the linear regression test, it was discovered that p-value = 0.000 <0.05, so it was concluded that there was an effect of the addition of pineapple fruit and leaves of kesum on acid number content with an effect of 76.4% on the acid number, 71.4% on the peroxide number, and 81.5% to the saponification number. It is recommended to test the water content, free fatty acids, and iodine number.